TRENDS IN THE DEVELOPMENT OF DIGITAL TECHNOLOGIES (Лучшие интеллектуальные исследования, 2025)
Abstract: This article discusses the issues of Cybersecurity in the digital world and the stages and trends in the development of digital technologies.